What does it cost to ensure salt marsh migration? Using hedonic modeling to inform cost-effective conservation. (15th May 2020) - Gardner, George; Johnston, Robert J.
Abstract: The preservation of salt marshes under rapid sea-level rise (SLR) typically requires the conservation of marsh transgression zones—undeveloped uplands onto which marshes can migrate. Optimal planning for conservation of this type requires information on the expected benefit of marsh conservation and the cost of land suitable for marsh migration in particular areas. While information is available on marsh benefits within the literature, prior research provides little insight on associated land conservation costs. The coastal hedonic pricing literature focuses primarily on developed land, and there are no models designed to predict the cost of conserving land suitable for marsh migration. This paper develops a hedonic property value model to predict cost and explore price patterns associated with purchases of undeveloped land suitable for salt marsh migration under SLR. The model is illustrated using a case study from the Eastern Shore of Virginia, with a dataset consisting of open-market sales of undeveloped land from 2014 to 2017. Particular attention is paid to characteristics that determine marsh migration potential such as coastal distance, elevation and connectivity. Results demonstrate the insight for conservation planning that can be provided by models of this type and the errors associated with the use of simplified proxies to predict conservation costs of land suitable for marsh migration. Highlights: Salt marsh sustainability requires preserved land suitable for marsh migration. Planning for optimal preservation requires an ability to predict preservation cost. Model predicts the cost of preserving undeveloped land suitable for marsh migration. Cost predictions are more accurate than those provided by simpler methods. Model suggests options to improve the cost-efficiency of salt marsh conservation.